Plan B(ruxellles): Belgian intelligence and the terrorist attacks of 2015-16 - Lasoen, Kenneth (Terrorism and political violence, 2020)
This essay uses the official reports as well as sources from the intelligence services to provide a clearer picture of the working circumstances of the Belgian intelligence and security services and the pressure they were under to deal with the challenges posed by violent radicalisation and terrorist plots since the emergence of the foreign fighters phenomenon. It will be shown how mounting pressure from the rapidly expanding threat exacerbated the gradual exhaustion of the security services by structural issues of unaddressed organisational difficulties, and budget restrictions faced with increasing workloads. Due to the high number of foreign fighters, belated initiatives taken to assess the threat were impeded by barriers to information exchange, unclear guidance, and data overload. The failure of Belgian intelligence to detect the attack plans was more a symptom of policy failure than the underachievement of the services. A concluding section will reflect upon the inadequacy and lateness of policy responses because of a Belgian tendency to understate security.